2007
DOI: 10.1007/s10620-007-9991-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene Delivery to Intestinal Epithelial Cells In vitro and In vivo with Recombinant Adeno-Associated Virus Types 1, 2 and 5

Abstract: Intestinal disorders such as inflammatory bowel disease (IBD) result in chronic illness requiring lifelong therapy. Our aim was to evaluate the efficacy of recombinant adeno-associated virus (AAV) vector-mediated gene delivery to intestinal epithelial cells in vitro and in vivo. Human colon epithelial cell lines and colon biopsies were transduced using AAV pseudotypes 2/1, 2/2, and 2/5 encoding green fluorescence protein (GFP). Mice were administered the same vectors through oral, enema, intraperitoneal (IP) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…Furthermore, interaction of hu-G3BP with rAAV-6 led to the formation of aggregates and hampered transduction when the two were codelivered into the mouse. Based on these data, we propose that species-specific interactions of AAVs with blood proteins may differentially impact vector distribution and efficacy in different animal models.T he recombinant adeno-associated vector (rAAV) platform, derived from a nonpathogenic dependovirus, has many attributes suitable for in vivo gene transfer: rAAV vectors are capable of transducing a wide range of cell types, including dividing and nondividing cells; rAAV genomes persist as episomal chromatin in the nucleus of transduced cells (38); and stable, persistent expression has been reported for many transgenes in different tissues and species (6,12,36,39). rAAVs have proven to be efficient in preclinical studies in animal models (16,28), and results from clinical trials are promising (7,47).…”
mentioning
confidence: 99%
“…Furthermore, interaction of hu-G3BP with rAAV-6 led to the formation of aggregates and hampered transduction when the two were codelivered into the mouse. Based on these data, we propose that species-specific interactions of AAVs with blood proteins may differentially impact vector distribution and efficacy in different animal models.T he recombinant adeno-associated vector (rAAV) platform, derived from a nonpathogenic dependovirus, has many attributes suitable for in vivo gene transfer: rAAV vectors are capable of transducing a wide range of cell types, including dividing and nondividing cells; rAAV genomes persist as episomal chromatin in the nucleus of transduced cells (38); and stable, persistent expression has been reported for many transgenes in different tissues and species (6,12,36,39). rAAVs have proven to be efficient in preclinical studies in animal models (16,28), and results from clinical trials are promising (7,47).…”
mentioning
confidence: 99%
“…Previous attempts at delivery of agents to the intestinal epithelium via oral, intraperitoneal injection, and systemic injection have not yielded good results. 3,6,11,16 Administration of insoluble agents by rectal enema have demonstrated uptake in the rectum only and thus is not a optimal approach for broader colonic administration. 17 Although the isolated SMA injection technique effectively reached the small bowel and colon, these data also demonstrate that there is systemic escape, albeit in low levels.…”
Section: Discussionmentioning
confidence: 99%
“…Sferra et al 8 reported the successful SMA injection in a rat for vector administration and thus we developed and reported the first isolated SMA injection in a mouse model. 11 To improve our efficiency and hasten postoperative recovery we have developed a modified microsurgical approach. Here we report the detailed steps for this surgical approach to verify the anatomical distribution, evaluate the biodistribution, and examine the feasibility of administering biological agents following SMA injection.…”
mentioning
confidence: 99%
“…Successful transduction of the rabbit lung [61,62], and the rat carotid arteries [63] by AAV2 vectors was also reported in 1997. Subsequently, various AAV serotype vector-mediated gene transfer in various cell cells and tissues, such as intestinal epithelial cells [64], pancreatic beta cells [65], salivary glands [66], maxillary sinus [67] and temporomandibular joints [68], and in various animal models, such as hamster [69], Japanese quail [70], gerbil [71], cat [72], dog [73], and cynomolgus monkeys [74] and were also reported. A representative example of some of these studies with the various AAV serotype vectors in the most commonly used animal models is depicted in Figure 1.…”
Section: Main Textmentioning
confidence: 99%